Calculation in Agrocluster System in Uzbekistan - Abdukhalilovich, Sultonov Shodiyor; Axtam-o’g’li, Rasulev Umidjon (European Journal of Life Safety and Stability (2660-9630), 2023)
In the article based on the study of theoretical views of economic entities, necessities, principles of development and conditions, stages and evaluation of efficiency, developed extended and advanced definition of agro cluster as well as on the basis of ordering general features identified the main directions of government support.